2022
DOI: 10.1101/2022.07.19.500484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tecovirimat is highly efficient on the Monkeypox virus lineage responsible for the international 2022 outbreak

Abstract: The ongoing monkeypox virus (MPXV) outbreak is the largest ever recorded outside of Africa. Genomic analysis revealed a divergent phylogenetic lineage within clade 3, and atypical clinical presentations have been noted. We report the sequencing and isolation of the virus from the first clinical case diagnosed in France in May 2022. We tested the in vitro effect of tecovirimat (ST-246), a FDA approved drug, against this novel strain, showing efficacy at the nanomolar range. In comparison, cidofovir showed activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…309,[313][314][315][316][317] Tecovirimat has a distinguished antiviral effect against the monkeypox virus lineage responsible for the 2022 outbreak in vitro. 318 Further, the effectiveness and safety of tecovirimat has been revealed in multiple animal studies. [319][320][321][322][323][324] Treatment with 10 mg per kilogram of body weight of tecovirimat for 14 days in the monkeypox model could achieve >90% survival.…”
Section: Treatmentmentioning
confidence: 99%
“…309,[313][314][315][316][317] Tecovirimat has a distinguished antiviral effect against the monkeypox virus lineage responsible for the 2022 outbreak in vitro. 318 Further, the effectiveness and safety of tecovirimat has been revealed in multiple animal studies. [319][320][321][322][323][324] Treatment with 10 mg per kilogram of body weight of tecovirimat for 14 days in the monkeypox model could achieve >90% survival.…”
Section: Treatmentmentioning
confidence: 99%
“…All members of the Orthopoxvirus genus share the viral F13 target, which provides a rationale for utilizing surrogate orthopoxviruses to test the effectiveness of tecovirimat 76 . Recent research revealed that Tecovirimat is very effective against the MPXV lineage that caused the global 2022 outbreak 120 …”
Section: Monkeypox Therapeutic Drug Targets and Strategiesmentioning
confidence: 99%
“…Monkeypox is caused by Monkeypox virus (MPXV), a member of the Orthopoxvirus genus of the Poxviridae family and results in pox-like skin lesions, making the diagnosis difficult with chickenpox virus infection. , MPXV is endemic in a dozen countries in West and Central Africa . The 2022 outbreak virus belongs to MPXV clade 3 (within the formerly designated “West African” clade, which also includes clade 2). MPXV belonging to clade 1 (formerly designated “Congo Basin” clade) is associated with more severe disease compared to clades 2 and 3. ,,, This Monkeypox outbreak was reported on May 7, 2022, in the United Kingdom . Since June 27, 2022, Monkeypox cases have been reported to the World Health Organization (WHO) in 43 member states for which Monkeypox was not endemic .…”
Section: Introductionmentioning
confidence: 99%